Compensación Salarial de los Asaderos en el Departamento del Meta, Colombia (2013)
The work includes the analysis of wage compensation system of Asoasaderos Asaderos Meta Associates , associated entity currently 180 of them to meet the objectives descriptive research was applied on the total population , for which we used data collection instruments through which characterized the broilers and found that the level of education of the employees and managers of these organizations does not meet the technical or college level where informal labor issues is reflected in daily or wage payment , the existence of oral contracts , the frequency with which wages are canceled among other variables. The weaknesses identified are lack of staff education and strengths are geared towards population growth occurring in the region.